Indigenous Peoples and the Geographies of Power: Mezcala's Narratives of Neoliberal Governance. Autora del libro: Inés Durán Matute - Velasco Ortiz, Laura (Estudios Sociológicos de El Colegio de México, 2019)
Es una reseña